2015
DOI: 10.1371/journal.pone.0126282
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics, Physical Fitness and Motor Coordination of 9 to 11 Year Old Children Participating in a Wide Range of Sports

Abstract: ObjectivesThe aim of this study was to investigate to what extent 9 to 11 year old children participating in a specific sport already exhibit a specific anthropometric, physical fitness and motor coordination profile, in line with the requirements of that particular sport. In addition, the profiles in children with a different training volume were compared and possible differences in training hours per week between children from a low, moderate, and high level of physical fitness and motor coordination were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 36 publications
(45 reference statements)
5
70
1
8
Order By: Relevance
“…The research includes two important age-and sport-related contributions. Firstly, in the study by Opstoel et al [13], the athletes were 9-11 years old, whereas the current study involved older athletes (i.e. 11-14 years old).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The research includes two important age-and sport-related contributions. Firstly, in the study by Opstoel et al [13], the athletes were 9-11 years old, whereas the current study involved older athletes (i.e. 11-14 years old).…”
Section: Introductionmentioning
confidence: 85%
“…More specifically, the current study was designed to extend the findings of Opstoel et al [13], also by investigating whether children and adolescents who intensively engage in different sports demonstrate variation in motor coordination skills as measured by the KTK-test battery. The research includes two important age-and sport-related contributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationship has also been investigated between the degree of motor coordination and performance in different sports [11], such as tennis [12,13], table tennis [14], soccer [15], gymnastic [16,17], judo [18], and volleyball [19]. Overall, these findings have suggested that the degree of motor coordination is an important predictor of sports performance in youth athletes.…”
Section: Introductionmentioning
confidence: 98%
“…However, physical fitness in sport has a more specific definition, and its correlation with performance has been investigated in previous studies [2,9,13,23,24,27]. In this sense, some components needed to practice field hockey at a high level of performance are: agility to perform quick changes of direction without loss of speed, efficiency to recover between sprints, endurance of the stabilizing muscles of the spine to maintain the adopted posture during practice, and technical skills [18].…”
Section: Introductionmentioning
confidence: 99%